"Let the Discussion Continue, of Course, but Let the Organizing Begin": A Praxis Response. Issue 3 (September 2015) - Paul, Eric; Newfield, Marcia; Berry, Joe; Kroik, Polina
<x xml:space="preserve">Abstract</x> This piece builds on Richard Moser's essay, "A Shot at Strategy, " by discussing some basic organizing practices. It suggests that while it is critical we know why we should organize contingent faculty and students and that we be aware of some tactics that could be used in this movement, it is just as important to know how to organize. The essay looks at the first steps one would need to begin to organize a campus: outreach, one‐to‐one conversations, leadership development, and campaign planning. It also provides a list of resources to learn more about the organizing craft.